An ant–plant mutualism through the lens of cGMP-dependent kinase genes - Malé, P; Turner, K; Doha, M; Anreiter, I; Allen, A; Sokolowski, M; Frederickson, M (Royal Society, 2017)
In plant–animal mutualisms, how an animal forages often determines how much benefit its plant partner receives. In many animals, foraging behaviour changes in response to foraging gene expression or activation of the cGMP-dependent protein kinase (PKG) that foraging encodes. Here, we show that this highly conserved molecular mechanism affects the outcome of a plant– animal mutualism.We studied the two PKG genes of Allomerus octoarticulatus, anAmazonian ant that defends the ant–plant Cordia nodosa against herbivores. Some ant colonies are better ‘bodyguards’ than others. Working in the field in Peru, we found that colonies fed with a PKG activator recruited more workers to attack herbivores than control colonies. This resulted in less herbivore damage. PKG gene expression in ant workers correlated with whether an ant colony discovered an herbivore and how much damage herbivores inflicted on leaves in a complex way; natural variation in expression levels of the two genes had significant interaction effects on ant behaviour and herbivory. Our results suggest a molecular basis for ant protection of plants in this mutualism.